Comets and the Origin of Life by Janaki Wickramasinghe, Chandra Wickramasinghe, and William Napier - Dick, Steven J. (Journal of Scientific Exploration, 2012)
This volume is the latest in a series of books and articles stretching back more than three decades on a theme quite startling in its claims and implications: that terrestrial life did not originate on Earth but arrived in the form of cells or bacteria from outer space. The idea of “panspermia,” that the seeds of life are spread from planet to planet, dates to the 19th century with the ideas of Lord Kelvin. It was championed by the Swedish physicist, chemist, and Nobelist Svante Arrhenius at the beginning of the 20th century. Once scientists recognized the difficulties of life surviving in the conditions of interplanetary and interstellar space, by the 1960s a neo-panspermia became popular: not life itself, but prebiotic chemicals were the new seeds of life, made more likely by the discovery of numerous complex organic molecules in meteorites, comets, and interstellar molecular clouds. But the difficulties of synthesizing anything more complicated than amino acids in the wake of the famous Miller-Urey experiment in 1953 kept alive the idea that life itself may be spread throughout the universe. At the center of this work is Chandra Wickramasinghe, a research student of the maverick astronomer Fred Hoyle. In 1962 Hoyle became interested in the origin and nature of interstellar dust, in particular as found in dense molecular clouds, and he and Wickramasinghe set to work on the problem. They became convinced that dust could not form inside molecular clouds, but must have originated in the atmospheres of cool stars, protoplanetary discs, or supernova ejecta, a theory now widely accepted. It was the next steps that became increasingly controversial: that the spectroscopic signature of dust was best explained by complex biomolecules such as cellulose; that biomolecules were assembled into still more complex forms inside comets; and that the living cells and bacteria generated there were responsible for the origin of life on Earth. And not only that: Hoyle and Wickramasinghe argued that the delivery of bacteria from space continues, affecting both the origin and the ongoing evolution of life, and may even be responsible for certain diseases on Earth. These theories were not only reported in reputable scientific journals such as Nature, but also in popular books including Lifecloud (1978), Diseases from Space (1979), and Evolution from Space (1981). Biologists were not impressed; Lynn Margulis, not known for the timidity of her own theories such as endosymbiosis, called the first book “wanton, amusing, promiscuous fiction.”